Effects of the coach substitution on the technical - tactical and physical performance of professional teams in LaLiga - Martín Castellanos, A.; Muriarte Solana, D.; Mon López, D.; Marquina Nieto, M.; López del Campo, R.; Resta Serra, R.; García Aliaga, A. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: High-performance football is demanding and depends on several factors (1). The role of the coach is to achieve high levels of performance according to the club´s objectives, which are related with results (2). When the performance is not optimal, one of the strategies to address the problem is to change the coach, looking for a "winning effect" (3) in the following matches to improve the results achieved. The aim of the study is to analyse the effects of replace the coach, in the technical, tactical, and physical aspects, with the hypothesis that these performance variables would be increased.